Pengaruh Permainan Tradisional Neka Terhadap Kemampuan Sosial Anak Usia 5-6 Tahun - Loumani, Lois; Sutisna, Icam; Juniarti, Yenti (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2024)
The purpose of this study is whether there is an influence of traditional Neka games on the social abilities of children aged 5-6 years at Pembina State Kindergarten in Gorontalo City. This research is a quantitative experimental research (one group pretest-posttest design). The results of the study with a sample of 20 children showed an increase in the average pretest and posttest results. This can be seen in the pretest data obtaining an average value of 21.23 and a standard deviation of 3.783. Meanwhile, the posttest data obtained an average value of 29.17 and a standard deviation of 3.940. These results prove that there is a significant effect before and after the treatment. Based on the output of the Statistics Test, the results of the significant test obtained a calculated T value = 13.62, while the T table value was at (α) = 0.05, which was 2.036. So T count ≥ T table 13.62 ≥ 2.036 or p- value> alpha 20 > 0.05 in other words T count > T table then H0 is rejected or H1 is accepted, meaning that the hypothesis is accepted. Thus, the research hypothesis states that there is an influence of traditional Neka games on the social abilities of children aged 5-6 years at the State Kindergarten Pembina Kota Gorontalo.